2013
DOI: 10.19027/jai.11.141-152
|View full text |Cite
|
Sign up to set email alerts
|

Growth and viability of juvenile humpback grouper (Cromileptes altivelis) supplemented with inorganic and organic selenium

Abstract: This study was conducted to determine the effects of inorganic selenium (sodium selenite) and organic selenium (selenomethionine) supplementation on growth and viability of juvenile humpback grouper (Cromileptes altivelis). The experiment was designed as a completely randomized design with eight treatments and three replications. The treatment being tested was source and dosages of selenium ie., inorganic selenium (sodium selenite) supplementation with dosages of 0.5, 1, 2, and 4 mg Se/kg diet and organic sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Previous studies showed that Se could be used as a dietary supplement for various aquaculture organism such as rainbow trout (Nazari et al, 2016), channel catfish (Gatlin & Wilson, 1984), grouper (Hamzah et al, 2012), barramundi (Ilham et al, 2016), crucian carp (Zhou et al, 2009), Atlantic salmon (Sele et al, 2018), common carp (Ashouri et al, 2015), Nile tilapia (Lee et al, 2016;Iqbal et al, 2017), oriental river prawn (Kong et al, 2017), black seabream juvenile (Lee et al, 2008), common barbell (Kouba et al, 2014), and golden pompano (Wang et al, 2016). In this regard, the present study aimed to evaluate the effect of dietary organic selenium supplementation on the growth performance and protein utilization of African catfish juvenile fed with different protein level diets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that Se could be used as a dietary supplement for various aquaculture organism such as rainbow trout (Nazari et al, 2016), channel catfish (Gatlin & Wilson, 1984), grouper (Hamzah et al, 2012), barramundi (Ilham et al, 2016), crucian carp (Zhou et al, 2009), Atlantic salmon (Sele et al, 2018), common carp (Ashouri et al, 2015), Nile tilapia (Lee et al, 2016;Iqbal et al, 2017), oriental river prawn (Kong et al, 2017), black seabream juvenile (Lee et al, 2008), common barbell (Kouba et al, 2014), and golden pompano (Wang et al, 2016). In this regard, the present study aimed to evaluate the effect of dietary organic selenium supplementation on the growth performance and protein utilization of African catfish juvenile fed with different protein level diets.…”
Section: Introductionmentioning
confidence: 99%
“…Pro-oxidants produce free radicals (superoxides, hydroperoxides, and others) that can react with surrounding molecules such as proteins, fats, carbohydrates and DNA. The formation of free radicals will be neutralized by normal endogenous antioxidants, but if excessive it will cause oxidative stress that ultimately leads to local damage, organ dysfunction and death in fish (Hamzah et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of selenium to increase the growth rate and survival rate of the fish has been investigated by Hamzah et al (2012a) and Suprayudi et al (2013). Hamzah et al (2012a) reported that the supplementation of organic selenium to juvenile humpback grouper at 4 g Se/kg of feed resulted greater protein retention compared to other treatments. Furthermore, another study also showed increasing selenium supplementation to a certain level resulted a positive correlation with protein retention (Ilham et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Stress conditions in fish can lead to decreasing immune systems and antioxidants, causing them to be vulnerable (Tang et al, 2018). In addition, selenium is also an integral part of the enzyme glutathione peroxidase (GPx) which plays a role in the cellular defense process against oxidative damage to the cytoplasmic structure (Hamzah et al, 2012). There are two types of selenium, namely organic and inorganic selenium.…”
Section: Introductionmentioning
confidence: 99%
“…The biopeptides also have various functional roles, such as antihypertensive, antioxidant, and antimicrobial (Tamam et al, 2018). The effects of the dietary organic selenium have been studied on several aquaculture organisms, including tilapia Oreochromis niloticus (Suprayudi et al, 2013), humpback grouper Cromileptes altivelis (Hamzah et al, 2012), juvenile abalone Haliotis discus hannai Ino (Wang et al, 2012), white shrimp Litopenaeus vannamei (Kemal et al, 2023), and juvenile catfish Clarias gariepinus (Kemal, 2020).…”
Section: Introductionmentioning
confidence: 99%